Authentic leadership and performance: the mediating role of employees' affective commitment. Issue 1 (5th March 2018) - Ribeiro, Neuza; Gomes, Daniel; Kurian, Shaji
Abstract : Purpose: This study aims to examine the relationship between authentic leadership (AL), affective commitment and individual performance. More specifically, this study aims to understand how AL influences employees' affective commitment, how AL influences individual performance, how affective commitment influences individual performance and how affective commitment mediates the relationship between AL and individual performance. Design/methodology/approach: In total, 212 Portuguese employees participated in this study. A quantitative methodology was used. Baron and Kenny's linear regression method and Sobel test were used to test the mediation relationship. Findings: The results reveal that affective commitment mediates the relationship between AL and employees' performance. In others words, leaders' authenticity promotes employees' affective commitment, which, in turn, increases their individual performance. Practical implications: This research has practical implications for human resource management in organizations, particularly in selection processes and training of leaders and managers. Practitioners looking to increase employee commitment and performance can do so by augmenting the AL. Originality/value: This study enriches the knowledge about the relevance of emerging areas such as AL theory and responds to the need to understand underlying mechanisms linking AL with workers' commitment and performance (i.e. testing the construct's nomological network).